Shelf-life estimation of jelly drink formulated with bay leaf ( Syzygium polyanthum) and guava juice (Psidium guajava) - Putri Sefanadia; Anna Marliyati Sri; Setiawan Budi (BIO Web of Conferences, 2025)
Jelly drinks must meet two essential requirements: safety and quality during storage and distribution. This study aimed to investigate the shelf life of jelly drinks containing a 50:50 ratio of bay leaf extract and guava juice at various storage temperatures. The study employed a completely randomized design (CRD) with two variables: storage temperature (4°C and 25°C) and duration (0, 2, 4, 6, 8, and 10 days). The pH, sensory, and microbiological characteristics of the jelly drinks were analyzed. The results indicated that storage temperature did not significantly affect sensory characteristics. Jelly drinks stored at both room and refrigerated temperatures were well accepted and considered commercially viable. The maximum shelf life was eight days under refrigeration, while at room temperature (25°C), it reached the SNI threshold after four days. Antimicrobial agents are recommended to extend the shelf life of the Jelly Drink made from bay leaf and guava juice (GUALAM).